Arab dress : a short history : from the dawn of Islam to modern times - Stillman, Yedida Kalfon, 1946-1998 (Themes in Islamic studies ;, 2003)
This richly illustrated volume is a historical and ethnographic study of one important aspect of Arab-Islamic material culture - clothing. Surveying the evolution, transformations, and semiotics of modes of dress over 1400 years throughout the Middle East, North Africa, and medieval Islamic Spain.